Effect of different capacitating agents on in vitro fertilization of goat follicular oocytes - PAWSHE, C H; TOTEY, S M (The Indian Journal of Animal Reproduction, 2023)
The present investigation is an attempt to establish optimal culture conditions for in vitro fertilization (!VF) of goatoocytes. Ovaries were obtained from a slaughter house and cumulus oocytes complexes (COCs) were washed three times in TLHEPESmedium and were matured for 24 h in TCM-199 (M-199) media supplemented with 10% fetal calf serum (FCS) andhormones (I mg/ml 17/3 estradiol, E2; 0.5 mg/ml ml follicle stimulating hormones (FSH) and 5.0 mg/ml leutinizing hormone, LH).After 24 hrs. of incubation oocytes were inseminated with percoll separated epididymal spermatozoa in Brackett and Oliphant (BO)or Talp-fertilization medium and treated with either Ca++ ionophore (A-23187) (0.1, 0.2 and 0.5 mM/ml + 5mM caffeine / L ) orheparin (0,1,10 and 100 mg/ml)+ 5mM caffeine IL or heparin (0,1,10 and I00mg/ml) alone in Talp-fertilization medium.
Keywords: Goat; oocyte; maturation; fertilization; capacitation